Proteinase-Activated Receptor-2-Triggered Prostaglandin E2 Release, but Not Cyclooxygenase-2 Upregulation, Requires Activation of the Phosphatidylinositol 3-Kinase / Akt / Nuclear Factor-κB Pathway in Human Alveolar Epithelial Cells - Kazumi Moriyuki; Fumiko Sekiguchi; Kaori Matsubara; Hiroyuki Nishikawa; Atsufumi Kawabata (Elsevier, 2009)
Proteinase-activated receptor-2 (PAR2) triggers upregulation of cyclooxygenase-2 (COX-2) and prostaglandin E2 (PGE2) formation in human alveolar epithelial A549 cells. This COX-2 upregulation appears to involve the Src / epidermal growth factor (EGF) receptor / p38 MAP kinase (p38MAPK) pathway and also the cAMP-response element-binding protein (CREB) pathway. Here, we investigated the roles of nuclear factor-κB (NF-κB)-related signals in the PAR2-triggered PGE2 release / COX-2 upregulation in A549 cells. The PAR2-triggered PGE2 release was clearly blocked by an inhibitor of the NF-κB pathway. Stimulation of PAR2 actually caused phosphorylation of inhibitor-κB, an indicator of NF-κB activation, an effect being blocked by inhibitors of MEK, phosphatidylinositol 3-kinase (PI3-kinase), and Akt, but little or not by inhibitors of p38MAPK and JNK. Stimulation of PAR2 also caused phosphorylation of Akt, an effect suppressed by inhibitors of PI3-kinase and MEK. Nonetheless, the PAR2-triggered upregulation of COX-2 was resistant to inhibitors of NF-κB, PI3-kinase, and Akt, but was attenuated by inhibitors of MEK and JNK. Stimulation of PAR2 induced phosphorylation of CREB, an effect abolished by an inhibitor of MEK but not inhibitors of p38MAPK and EGF receptor. These findings demonstrate that the MEK / ERK / PI3-kinase / Akt / NF-κB pathway is involved in PAR2-triggered PGE2 formation, but not upregulation of COX-2 that is dependent on activation of ERK/CREB and JNK in addition to p38MAPK. Keywords:: proteinase-activated receptor-2 (PAR2), nuclear factor-κB (NF-κB), prostaglandin E2 (PGE2), cyclooxygenase-2 (COX-2), human alveolar epithelial cell line A549